Dennett's compatibilism considered - Puttergill, Julian Gatenby (Rhodes University, Faculty of Humanities, Department of Philosophy, 1997)
My basic concern in this thesis is to examine the details behind Dennett's attempt to reconcile the notions of mechanism and responsibility. In the main this involves an examination of how he tries to secure a compatibilism between mechanistic and intentional explanations by developing a systematised conception of intentional explanation. I begin by briefly discussing the various notions needed for understanding what is at stake in the area and where the orthodoxy on the matter lies. As such the first three sections of the work are not focussed on Dennett's work itself and playa stage-setting role for the deeper work to follow. These notions include the likes of the rationale behind attributing moral responsibility, agency and action, mechanism and mechanistic explanation, and intentional explanation. I suggest that the basic intuition regarding mechanism and responsibility is such that the two are seen to be incompatible with each other. The main reason for this lies in an intuition that mechanism undermines intentional explanation and so renders the notion of action largely empty. Action, I show, is at the heart of our attribution of responsibility and is dependent on intentional explanation. Having presented these issues, I turn to the details of Dennett's 'intentional systems theory'. I argue that Dennett attempts to avoid the intuition that mechanism is incompatible with responsibility by developing a specialised account of intentional explanation. Dennett calls it the intentional stance. r highlight the two important features of this intentional stance, namely rationality and intentionality. r show that Dennett's position on rationality and intentionality is such that it does allow him to secure an explanatory compatibilism between mechanism and his sort of intentional explanation. I argue, however, that his sort of intentional explanation does not fulfil our requirements for ascribing agency or moral responsibility. This is accomplished in part by developing alternative conceptions of the two notions. Out of this I develop a different sort of intentional stance, which I call the folk stance. I show finaIly that Dennett's compatibilist move is incapable of being applied to the folkstance from which we do in fact make attributions of responsibility, and so conclude thatDennett fails to make the case for reconciling mechanism and responsibility.
Keywords: Dennett, Daniel Clement; Intentionality (Philosophy)